Penerapan Prinsip Kodrat Alam dan Kodrat Zaman dalam Pendidikan yang Sesuai dengan Pemikiran Ki Hadjar Dewantara - gupitasari, tressa pratywi; Munawarah, Siti; Kurnia Putri, Sonia; Gentari Febriani, Vini; Aulia Su’adah, Zeni (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2025)
The application of the principles of Nature and the Nature of the Times is based on Ki Hadjar Dewantara's philosophy. This research aims to analyze the implementation of these two principles in the current education system, particularly in creating a balance between developing 21st-century skills and maintaining students' fundamental values. The research method used is a literature study examining Ki Hadjar Dewantara's works, relevant scientific journals, and national education policy documents such as the Freedom Curriculum. Research results show that although the principles of Nature and the Nature of the Times serve as philosophical foundations in education policy, their implementation still faces concrete challenges such as an evaluation system that is too cognitively oriented and teachers' limited competence in implementing student-centered learning. There is a need for curriculum development that provides autonomy to educational units, prioritizes project-based learning, and meaningfully integrates technology. Education based on the principles of natural disposition and zeitgeist is expected to produce students who are intelligent, have strong character, and are ready to face future challenges.